Acute Ischemic Stroke in Children Vs Young Adults - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Clinical characteristics, stroke etiology, and outcome (modified Rankin scale [0-6] score at 3-6 months) in children (1 month-16 years) and young adults (16-45 years) with arterial ischemic stroke (AIS) were compared in a multicenter study at University of Bern and other centers in Switzerland.